Development of a Fourier Transform Infrared (FT-IR) model for screening susceptible and resistant Eucalyptus clones against Chrysoporthe austroafricana - Naidoo, Sanushka (University of Pretoria, 2023)
Dissertation (MSc (Biotechnology))--University of Pretoria, 2022.